2018
DOI: 10.2196/cardio.8718
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction Support: Website Content Analysis

Abstract: BackgroundFood addiction has a long history; however, there has been a substantial increase in published literature and public media focus in the past decade. Food addiction has previously demonstrated an overlap with overweight and obesity, a risk for cardiovascular disease. This increased focus has led to the establishment of numerous support options for addictive eating behaviors, yet evidence-based support options are lacking.ObjectiveThis study aimed to evaluate the availability and content of support opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 43 publications
(74 reference statements)
0
22
0
2
Order By: Relevance
“…For instance, the implementation of a self-help support group through a structured program could promote mutual support between persons with FA, break isolation, and create a space for sharing experiences [ 144 ]. Some authors also reviewed the beneficial input of online support options for food addiction, as well as other forms of self-help groups and sessions [ 145 , 146 ]. The restriction, or even the relative reduction, of some specific foods seen as addictive for a specific patient could be an option, contrary to the current view which aims at reducing dysfunctional dieting in favor of regular eating with flexible and moderate food consumption with no forbidden foods [ 51 ].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…For instance, the implementation of a self-help support group through a structured program could promote mutual support between persons with FA, break isolation, and create a space for sharing experiences [ 144 ]. Some authors also reviewed the beneficial input of online support options for food addiction, as well as other forms of self-help groups and sessions [ 145 , 146 ]. The restriction, or even the relative reduction, of some specific foods seen as addictive for a specific patient could be an option, contrary to the current view which aims at reducing dysfunctional dieting in favor of regular eating with flexible and moderate food consumption with no forbidden foods [ 51 ].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Whereas, both medication studies, which included the combination of naltrexone and bupropion [ 38 ] and pexacerfont (a corticotropin-releasing factor (CRF1) antagonist) [ 31 ], and the lifestyle modification study which comprised of diet and physical activity [ 33 ], reported this significant reduction over a shorter time period (16 weeks or less). Although the limited results prevent recommendations, it is important to note that the studies included in this review used higher-quality designs, and involved health professionals (versus peer-based or self-help) as part of the intervention delivery, in contrast to the majority of the studies included in previous reviews [ 15 , 16 , 17 ]. However, the majority of the included studies were of neutral quality (n = 6) based on our risk of bias analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high levels of self-perceived FA, there is a need for treatments or management approaches to assist individuals to seek help. However, current interventions are limited, with the majority of available treatments lacking a scientific evidence approach or not utilising health professionals with expertise in behaviour change [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations